The Effects of Morning Assembly Activities on the Independence Character of Students (Pre-Experimental Designs at SMK Karya Mandiri Nusawungu) - Lisa Selina Nursiyami; Efi Miftah Faridli; Ratna Kartika Wati (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to determine the extent of morning assembly activities' effects on students' independent character. The method used in this research is Pre-Experimental Designs with a One-Shot Case Study design. The sample comprises 56% or 157 students from the total 10th-grade classes. Data collection techniques employed in this study include observation, interviews, documentation, and questionnaires. The data analysis method utilized is the Partial T-test. The results indicate that morning assembly activities impact the independent character of students at SMK Karya Mandiri Nusawungu. This conclusion is based on the Partial T-test results, which show a calculated T value of 18.043 compared to a table value of 0.67608 and a significance value of 0.000, which is less than 0.05, indicating that morning assembly activities significantly affect the independent character of students. Furthermore, the simple linear regression test results reveal a correlation value of 0.823 or 82.3%, which falls into the very high category. Additionally, the coefficient of determination (R Square) test results show a value of 67.7%, indicating that it is clear that variable X (morning assembly activities) affects variable Y (independent character). The high R Square value demonstrates that morning assembly activities significantly affect students' independent character.